2021
DOI: 10.1002/pits.22481
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of drama therapy services in the North American school system: Responses from the field

Abstract: Drama therapy is an emerging mental health practice in North American schools. Yet little research has focused directly on the role of drama therapists in schools or their service navigation practices and challenges. From February to July of 2018, drama therapists affiliated with the North American Drama Therapy Association currently working in North American schools were invited to participate in an online Qualtrics survey. A qualitative thematic analysis was conducted on open-ended response items, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…Numerous calls have focused on a public health approach to addressing traumatic stress among students in schools (e.g., Chafouleas et al, 2019 ; Kolbe, 2019 ). School-based drama therapy practitioners have targeted trauma and delivered services across a multi-tiered systems of support (MTSS) framework (e.g., Hoover et al, 2019 ) to address the impacts of adverse experiences on young students’ socio-emotional functioning (Frydman & Mayor, 2021 ). For example, researchers stressed the imperative of a public health model to address the whole school.…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous calls have focused on a public health approach to addressing traumatic stress among students in schools (e.g., Chafouleas et al, 2019 ; Kolbe, 2019 ). School-based drama therapy practitioners have targeted trauma and delivered services across a multi-tiered systems of support (MTSS) framework (e.g., Hoover et al, 2019 ) to address the impacts of adverse experiences on young students’ socio-emotional functioning (Frydman & Mayor, 2021 ). For example, researchers stressed the imperative of a public health model to address the whole school.…”
Section: General Findingsmentioning
confidence: 99%
“…In a recent survey of SBDT practitioners, ecological integration into schools was noted as needing development, specifically improvements in professional collaboration and accessing physical spaces (Frydman & Mayor, 2021 ). In contrast, articles in this review indicated working alongside allied school-based professionals to deliver SBDT (Ellinor, 2019 ; Lau, 2019 ) and support assessment (Johnson et al, 2021 ; Moula et al, 2020 ).…”
Section: General Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, school‐based CAT programs are often individually structured to respond to their specific school environments (Glassman & Prasad, 2013; Isis et al, 2010; Johnson et al, 2020; Nelson, 2010; Sajnani et al, 2019). For example, North American drama therapists articulate their role as being reactive supports in schools, often positioned as responsive to emergent needs of individual students, within classrooms, or as called for on a school‐wide basis (Frydman & Mayor, 2021). Specific programs that feature drama therapy (Burch et al, 2019; Dean et al, 2019; Johnson et al, 2020; Sajanai et al, 2019) and dance/movement therapy (Dean et al, 2019; Kornblum & Halsten, 2006) characterize themselves as a recommended service that regularly receives referrals from their school‐based colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…However, these programs have often been funded externally or had a shorter‐term presence in the school setting and generally operate as an outside contractor. Moreover, it is common for one‐time school‐related CAT interventions to be presented as a special project or time‐limited intervention (Beardall, 2011; Burch et al, 2019; Cook, 2020; Frydman & Mayor, 2021; Hylton et al, 2019; Mayor & Frydman, 2019; Pasiali & Clark, 2018).…”
Section: Introductionmentioning
confidence: 99%